Research of Social and Perceptive Abilities of Technical University Students - V. B. Sidorovich (Наука и техника)
The paper gives insight into social and perceptive abilities of a personality that are a part of professional competence of an engineer-to-be. These abilities ensure efficient interrelation with colleagues, administration, subordinates and assist to establish and support necessary business relations. They also make it possible to interpret and forecast correctly behaviour of partners in communication and successfully work in a team. The paper contains results of the investigations pertaining to social and perceptive abilities of the Belarussian National Technical University students.